Modulation effects of folic acid and vitamin D on the relationships between prenatal cumulative phthalate exposure and preschoolers’ emotional and behavioral problems - Li-wen Chen; Xin Chen; Chen Han; Bei-bei Zhu; Yi-fan Wang; Yuan Liu; Min-min Jiang; Ya-fei Wang; Chun-han Shan; Hua-yan Mo; Kun Huang; Hui Gao; et al. (Environment International)
Background: The results of current population-based studies exploring the effects of prenatal phthalate exposure on children’s behavioral problems are not completely consistent. In addition, it is not clear whether vitamins improve phthalate-induced health risks. Methods: This study was based on the Ma’anshan Birth Cohort, which included 2910 mother-child pairs. To assess children’s behavior, we used the Strengths and Difficulties Questionnaire (SDQ). A latent category growth model was used to model the scores of each subscale of the SDQ. Quantile g-computation and Bayesian kernel machine regression were applied to analyze the effect of prenatal cumulative phthalate exposure. Results: Prenatal cumulative phthalate exposure was associated with the “borderline and abnormal emotional symptoms” trajectory (β = 0.146, 95 % CI = −0.0003, 0.292), affecting girls more in emotional areas, and boys in conduct areas. There was an interaction effect between folic acid supplementation, vitamin D levels and phthalate mixtures on the risk of abnormal emotional behavior in children, which was reflected mainly in prosocial behavior and conduct problems. Conclusions: Prenatal cumulative phthalate exposure increased the risk of abnormal emotional symptoms in children, and there were sex differences. The duration of folic acid supplementation and vitamin D level can affect the effects of cumulative phthalate exposure on emotion and behavior.